PENGARUH BUDAYA ORGANISASI, KOMUNIKASI DAN PENGEMBANGAN KARIR TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. TAMAN BURUNG CITRA BALI INTERNASIONAL - Sapta Rini Widyawati; Putu Agus Eka Rismawan; I Wayan Remon Oktariana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Work morale is one of the keys to a company achieving its goals. If work morale is low it will hinder the organization from achieving its goals. Work morale will show the extent to which employees are passionate about carrying out their duties and responsibilities within the company. This study aims to determine the influence of organizational culture, communication and career development on employee morale at PT. Taman Burung Citra Bali International. The sample in this study amounted to 59 employees at PT. Citra Bali International Bird Park. Data collection was carried out through observation, interviews and questionnaires. The data analysis technique used was multiple linear regression analysis using the SPSS Version 25 program. Based on the results of this research analysis, it shows that organizational culture has a positive and significant effect on employee morale at PT. Taman Burung Citra Bali International. Communication has a positive and significant effect on employee morale at PT. Taman Burung Citra Bali International. Career development has a positive and significant effect on employee morale at PT. Taman Burung Citra Bali International.